2015
DOI: 10.1590/0102-311x00005114
|View full text |Cite
|
Sign up to set email alerts
|

Quanto custa para as famílias de baixa renda obterem uma dieta saudável no Brasil?

Abstract: O objetivo do estudo foi identificar o custo necessário para a obtenção de uma dieta saudável no Brasil e analisar o comprometimento dessa prática na renda familiar. Foram utilizados dados da Pesquisa de Orçamentos Familiares de 2008. Aquisições de alimentos foram coletadas durante sete dias em 55.970 domicílios. Dois subconjuntos compostos apenas por famílias de baixa renda (≤ R$ 415,00 per capita/mês e ≤ US$ 1,00 per capita/dia) foram analisados. A partir dos alimentos obtidos, foram calculados calorias, des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 21 publications
0
17
0
25
Order By: Relevance
“…A population-based study in Brazil, with probabilistic sample of 55,970 households from the POF of 2008-2009, has shown that family income and food prices influence the acquisition of healthy foods, especially among individuals of lower purchasing power 5 . Thus, in order to ensure the caloric contribution in the diet from food with high nutrient density (fruits, vegetables, and milk and dairy products), an increase in the income of the subjects would be needed, or the reduction in prices, as an adequate intake of these types of food creates an increase in expenditure 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population-based study in Brazil, with probabilistic sample of 55,970 households from the POF of 2008-2009, has shown that family income and food prices influence the acquisition of healthy foods, especially among individuals of lower purchasing power 5 . Thus, in order to ensure the caloric contribution in the diet from food with high nutrient density (fruits, vegetables, and milk and dairy products), an increase in the income of the subjects would be needed, or the reduction in prices, as an adequate intake of these types of food creates an increase in expenditure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to ensure the caloric contribution in the diet from food with high nutrient density (fruits, vegetables, and milk and dairy products), an increase in the income of the subjects would be needed, or the reduction in prices, as an adequate intake of these types of food creates an increase in expenditure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that increased income and lower prices of fruits and vegetables might improve their participation in the diet of Brazilians. Borges et al 26 analyzed the seven-day food acquisition of 55,970 families in 2008. Calories, expenses and average price were calculated and current and ideal expenditures were compared for the eight food groups proposed by the 2006 Brazilian food guide.…”
Section: Discussionmentioning
confidence: 99%
“…[...] Eu compro quatrocentos reais de remédio todo mês, quase o que eu recebo, então eu me alimento de acordo com meus probleminhas e minhas condições financeiras." (P1) Um estudo apontou que os brasileiros de baixa renda apresentam dificuldades de se alimentar corretamente com uma nutrição balanceada, conforme as recomendações nacionais, enquanto que os de média e alta renda gastam grande parte do seu dinheiro com alimentos pouco saudáveis (23) .…”
Section: Alimentação E Atividade Física Aliadas Ao Controle Do Diabetesunclassified